Light–dark (12:12) cycle of carbon and nitrogen metabolism in Crocosphaera watsonii WH8501: relation to the cell cycle - Anthony Dron; Sophie Rabouille; Pascal Claquin; Bertrand Le Roy; Amélie Talec; Antoine Sciandra (Environmental Microbiology, 2012)
Summary This study provides with original data sets on the physiology of the unicellular diazotrophic cyanobacterium Crocosphaera watsonii WH8501, maintained in continuous culture in conditions of obligate diazotrophy. Cultures were exposed to a 12:12 light–dark regime, representative of what they experience in nature and where growth is expected to be balanced. Nitrogen and carbon metabolism were monitored at high frequency and their dynamics was compared with the cell cycle. Results reveal a daily cycle in the physiological and biochemical parameters, tightly constrained by the timely decoupled processes of N 2 fixation and carbon acquisition. The cell division rate increased concomitantly to carbon accumulation and peaked 6 h into the light. The carbon content reached a maximum at the end of the light phase. N 2 fixation occurred mostly during the dark period and peaked between 9 and 10 h into the night, while DNA synthesis, reflected by DNA fluorescence, increased until the end of the night. Consequently, cells in G1‐ and S‐phases present a marked decrease in their C : N ratio. Nitrogen acquisition through N 2 fixation exceeded 1.3‐ to 3‐fold the nitrogen requirements for growth, suggesting that important amounts of nitrogen are excreted even under conditions supposed to favour balanced, carbon and nitrogen acquisitions.